JAVANESE FARMERS’ PRANATA MANGSA CONCEPT AS THE IDEAS OF WAYANG BEBER CREATION - Faris Wibisono; Basuki Teguh Yuwono (ARTISTIC : International Journal of Creation and Innovation, 2023)
Javanese farmers practice the pranatamangsaas their agricultural way. This conception has guided the Javanese agricultural approach in treating nature for generations from their ancestors to the present day. This teaching also inspires the creation of wayangbeberwith the sunggingtechnique. The creation process consists of three phases, namely (1) exploration, (2) design, and (3) realization. The resulting work is divided into 24 pejagongsand six scrolls of wayangbeber, with each pejagongcontaining a continuous narrative. The applied sunggingancolors represent the changing seasons, while the gununganof kala at the beginning and conclusion of each pejagong represents the change in time and setting. The descriptions are separated into various categories, including the farming community, village officials, religious leaders, and intermediaries.